TEACHING ENGLISH TO YOUNG LEARNERS BY MEANS OF SONGS AND FOLK TALES WITH INDONESIAN SETTINGS: INDONESIA – INDIA GLOBAL PROJECT PROGRAM - Erlyna Abidasari; Rina Wahyu Setyaningrum (Universitas Brawijaya, 2020)
Global Project (GO PRO) project mainly aims at creating competent students in four English skills with the global knowledge. One of the most pivotal aspects of GO PRO is live-video conference. The Indonesian classical songs and folktales were translated to English and performed in the conference representing Indonesian local wisdom. The teacher’s narrative writing was the source of this research data to explore how she organized the activities to support the live-video conference. To complete, semi-structured interview was employed for investigating the advantages of the event for the students’ experience in global communication. The data were narrated by grouping them in themes as it is suggested by the Narrative Inquiry design. It was found that GO PRO has benefitted students from Indonesia as the opportunity in performing the songs and folktale in English motivated them to practice their English more actively and frequently. For Indian students, it contributed to their new insight about Indonesian local wisdoms.